The Church of Scientology: Legitimacy through Perception Management. Issue 3 (14th February 2014) - Halupka, Max
Abstract In 1967 the Church of Scientology's tax-exempt status was revoked on the basis that it failed to meet the criteria outlined in section 501(c)(3) of the Internal Revenue Service. Between its loss, and eventual reacquisition in 1993, the Church of Scientology employed a number of political based tactics in an attempt to legitimize itself to the public sector. This article explores these tactics in relation to the religion's use of perception management. The article argues that the processes of both legal recognition and legitimization draw upon each other in a new faith's transition to mainstream theology. In this, the Church employed perception management in attempt to influence both processes. In exploring this, the paper contributes to our understanding of role that public legitimacy plays in a new faith's development.